2002
DOI: 10.1177/095632020201300506
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment with Novel Ribonucleotide Reductase Inhibitors Trimidox and Didox Reverses Late-Stage Murine Retrovirus-Induced Lymphoproliferative Disease with Less Bone Marrow Toxicity Than Hydroxyurea

Abstract: We evaluated the ability of a short course of treatment with the ribonucleotide reductase (RR) inhibitor hydroxyurea (HU) and two novel RR inhibitors Trimidox (TX) and Didox (DX) to influence late-stage murine retrovirus-induced lymphoproliferative disease. LPBM5 murine leukaemia virus retrovirus-infected mice were treated daily with HU, TX or DX for 4 weeks, beginning 9 weeks post-infection, after development of immunodeficiency and lymphoproliferative disease. Drug effects on disease progression were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Didox belongs to a unique class of more specific and more potent inhibitors of RR enzyme activity than hydroxycarbamide. Already Didox has demonstrated anti‐tumour activity in several tumour models in both in vitro studies and in vivo models (Elford et al , 1979; Mayhew et al , 1997, 2002; Horvath et al , 2004a,b; Sumpter et al , 2004; Wakisaka et al , 2005). Phase I trials, as well as phase II clinical studies, in patients with advanced breast cancer showed minimal toxicity (Veale et al , 1988; Carmichael et al , 1990; Rubens et al , 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Didox belongs to a unique class of more specific and more potent inhibitors of RR enzyme activity than hydroxycarbamide. Already Didox has demonstrated anti‐tumour activity in several tumour models in both in vitro studies and in vivo models (Elford et al , 1979; Mayhew et al , 1997, 2002; Horvath et al , 2004a,b; Sumpter et al , 2004; Wakisaka et al , 2005). Phase I trials, as well as phase II clinical studies, in patients with advanced breast cancer showed minimal toxicity (Veale et al , 1988; Carmichael et al , 1990; Rubens et al , 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Trimidox and didox have shown efficacy in combination with Temozolomide (an alkylating agent) in the treatment of human malignant glioma cell lines [279]. Trimidox and didox suppress retrovirus-induced murine AIDS with more effectiveness and less bone marrow toxicity than hydroxyurea [280][281][282]. Both of the agents also showed the ability to improve the efficacy of the reverse transcriptase inhibitor didanosine (2,3-didoxyinosine; ddI) and abacavir in murine AIDS model.…”
Section: Didox and Trimidoxmentioning
confidence: 98%
“…All three RNR classes also share a sophisticated allosteric regulation mediated by different deoxyand ribonucleotides, which guarantees an adequate and bal-anced supply of DNA precursors during DNA replication and repair. The essentiality of this enzyme makes it a good candidate for anticancer, antiviral, and antibacterial drug therapy (15)(16)(17). In P. aeruginosa, the investigation of the expression and physiological function of the three different classes of RNR is important from a biomedical and physiological point of view, since such studies might contribute to a better understanding of the pathogenicity and the metabolic diversity of this species.…”
mentioning
confidence: 99%